2009
DOI: 10.1155/2009/206505
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk of Cytomegalovirus Infection during Pregnancy in an Urban Area of Northern Italy

Abstract: The fetal consequences of CMV infection make it one of the most serious infections contracted during pregnancy, but the scientific community is divided over the proposed implementation of preventive screening for anti-CMV antibodies. The aim of this study was to assess the incidence and risk of infection during pregnancy in 2817 women who underwent anti-CMV IgG and IgM antibody screening during the period 2005–2007. The prevalence of anti-CMV IgG antibodies was 68.3% (95% CI: 66.6–70.0); the seroconversion rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 29 publications
8
28
0
Order By: Relevance
“…CMV IgG seroprevalence was significantly (X 2 =6.1, P=0.01) lower (89.5%) in women with frequent abortion (3-8) as compared to women (97.4%) non frequent abortion (1)(2). OR confirmed the association between CMV IgG seroprevalence and number of abortion (OR=4.39, P=0.01).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…CMV IgG seroprevalence was significantly (X 2 =6.1, P=0.01) lower (89.5%) in women with frequent abortion (3-8) as compared to women (97.4%) non frequent abortion (1)(2). OR confirmed the association between CMV IgG seroprevalence and number of abortion (OR=4.39, P=0.01).…”
Section: Discussionmentioning
confidence: 88%
“…The human cytomegalovirus (HCMV) is the most common congenital viral infection worldwide and may be asymptomatic forms (90% of cases) to severe fetal damage and, in rare cases, death due to abortion [1]. Cytomegalovirus (CMV) infection during pregnancy is far more complex than other infections, due to the ability of the virus to be frequently reactivated during the child bearing age and be transmitted to the fetus inspite of maternal immunity [2].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of HCMV infection in different geographical regions is shown in the world map (Fig. The prevalence of HCMV is 50-85% in the USA [28], 41% in the Netherlands [29], 63.7% in Germany [30], 68.3% in Italy [31] and 57% in both Australia [32] and Canada [33]. The prevalence of HCMV is 50-85% in the USA [28], 41% in the Netherlands [29], 63.7% in Germany [30], 68.3% in Italy [31] and 57% in both Australia [32] and Canada [33].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Tookey et al [12] performed in London revealed that HCMV seropositivity varied between different races: The seropositivity rates were 45.9% in white women, 88.2% in Asian women and 77.2% in black women (of African/Caribbean origin). Furthermore, the following international HCMV IgG seropositivity rates have been reported: 51.5% in French women, 68.3% in Italian women, 30.4% in Irish women, 63.5% in American women and 56.8% in Australian women [13][14][15][16][17]. In different regions of Turkey, HCMV seropositivity has been reported to be 84.3%-94.7% [18][19][20].…”
Section: Discussionmentioning
confidence: 99%